Endourological Management of Urogenital Carcinoma - Naito, S.; Naito, S.; Hirao, Y.; Hirao, Y.; Terachi, T.; Terachi, T. (Recent Advances in Endourology, 2006)
In the 6 years since the publication of the first volume of Recent Advances in Endourology by the Japanese Society of Endourology and ESWL, data on long-term oncological or functional outcomes have been collected in several related fields, and advances in surgical techniques and improved instrumentation have led to further development of such complex surgery as laparoscopic partial nephrectomy and radical prostatectomy. This seventh volume in the series focuses on the treatment of urogenital malignancies by endourological procedures, including laparoscopic surgery with robotic assistance. The standard procedures and their relatively long-term outcomes as well as new techniques have been clearly described with detailed references. This book provides a better understanding of the present status of endourological management for urogenital carcinoma and sets the stage for future improvements in both oncological and functional outcomes.